Konsep Jihad Lingkungan Sebagai Strategi Pencegahan Kerusakan Terumbu Karang di Indonesia - Baso Muhammad Nibras Abiyyu; Sukmawati Markun; Azman Arsyad; Lomba Sultan (Media Hukum Indonesia (MHI), 2026)
Coral reef degradation in Indonesia, part of the Coral Triangle region that holds 76% of the world's coral reefs, continues to rise due to both natural and anthropogenic factors. Conservation approaches relying solely on regulation and technology have proven insufficient without accompanying moral and spiritual awareness within society. This study aims to examine the concept of environmental jihad as a strategy for preventing coral reef damage in Indonesia through ontological, epistemological, and axiological philosophical perspectives. The method employed is descriptive-qualitative library research, analyzing primary sources from the Qur'an and Hadith alongside contemporary scientific literature on marine ecology and Islamic legal thought. The findings show that, ontologically, environmental jihad manifests humanity's responsibility as khalifah (steward) to preserve the balance of God's creation; epistemologically, the concept is constructed through the integration of revelation, scholarly ijtihad, the maq??id al-shar?'ah approach, and empirical scientific knowledge. This research is expected to enrich the discourse on environmental fiqh while encouraging the integration of religious values into Indonesia's marine ecosystem conservation policies.